NOTES ON MALAYSIAN CYPERACEAE - J. H. KERN (REINWARDTIA, 1952)
This is the first paper of a series, in which preparatory to a more comprehensive treatment for "Flora Malesiana," some noteworthy Malaysian Cyperaceae will be dealt with. It is based on the material of this family in the Herbaria at Bogor (BO), Leiden (L), and Singapore (S).My sincere thanks are extended to the Directors of these institutions for giving me the opportunity to study their rich collections.In 1935—36 Kiikenthal's excellent monograph on the genus Cyperus in Engler's "Pflanzenreich" appeared.Unfortunately that author revised only a few specimens of the herbaria already mentioned,so that the basis for the distribution of the genus in Malaysia, as given in his invaluable work, compares unfavourably with that of the species of other regions.Kiikenthal's delimitation of the genus is readily accepted; in general his arrangement of the species is also followed, although I cannot agree with Kiikenthal's assertion that his system should be in close accordance with the genetic development of the genus.On the whole only the synonymy important for the Malaysian region is given below. For a more complete account the reader is referred to Kiikenthal's monograph, in which of course the literature of merely regional interest could not always be fully considered.The accompanying plates are part of a series, drawn under mysupervision by two of the draughtsmen of Herbarium Bogoriense, Sukirno and Md. Anwar.